KATEGORISASI SEMANTIS VERBA MARAH DAN TURUNANNYA DALAM BAHASA BATAK TOBA: KAJIAN SEMANTIK - Tampubolon, Lidya Purnamasari; Mulyadi, Mulyadi; Dardanila, Dardanila (Center of Language and Cultural Studies, 2024)
This research aims to describe categorization semantics verb “mirip marah” (angry-like) in the Toba Batak language. Through the MSA theoretical framework. Research data, both oral and written, was obtained using the listening method and the proficient method with a list of questions consisting of two models, namely (1) the verb lexicon 'like angry' and (2) the verb construction 'like angry' (DCT: Discourse Copeletion Test) .All data was studied using the matching method and the agih method, then presented using formal and informal methods and tested using triangulation techniques. The research results show that the verb “ mirip marah” ('angry-like’) in the Toba Batak Language (BBT) is categorized with the component 'I don't want something like this to happen'. Then the category results are divided into three subcategories, namely: (1) subcategory 'I want something else now', (2) subcategory 'I want to say what I think about this' and (3) subcategory 'I want to do something'.